THE EFFECTIVENESS OF BRAIN SKETCHING TECHNIQUE IN WRITING DESCRIPTIVE TEXT - Ratu Yulianti Natsir (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This research aimed to find out the students’ improvement in writing descriptive text especially in content and organization by using Brain Sketching Technique. The problem statement of this research was how is the use of Brain-Sketching Technique improved the students’ skill in writing descriptive text. The researcher used quasi experimental design, and used two classes they were experimental class and control class, the data was collected by using written test. The pre-test was given to the students’ to find out the students’ improvement in writing process before the treatment and the post-test was given to find out the students’ improvement in writing process after the treatment. The population was the second year students of SMP Aisyiyah Paccinongang that consisted of 20 students in academic year 2014/2015. Meanwhile, the sample of this research was taken by using purposive sampling. The research findings indicated that the achievement of the second year students of SMP Aisyiyah Paccinongang, Gowa, improved after the use of Brain-Sketching Technique. It proven by the mean score of pre-test in experimental class was 67.12 and post-test was 77.32 and the mean score of pre-test in controlled class was 68.12 and post-test was 74.37. The statistical computations showed that Brain-Sketching Technique was likely effective to improve the students’ writing in descriptive text.